Performance of concrete containing microwaved sewage sludge ash as additional material - Muhammad Aizat, Azed (2021)
Urban population of Malaysia is stated as 72.8% of its total population, and growing every year. Malaysia itself produces 3.2 million m3 of sewage sludge annually. Normally all of this waste is disposed by using landfill method. This is a serious threat to environment due to the high toxic content of sewage sludge if disposed it without strict control. Furthermore, usual production of cement and sewage sludge ash consumes a lot of energy by using incineration process with a very high temperature. Thus microwave heating method seen as an alternatives use in this research to reduce the consumption of energy and time used to heat the sewage sludge ash. The aim of this study was to identify the optimum microwave temperature in producing Microwave Sewage Sludge Ash (MSSA), to determine the performances of varied percentage (0%, 5%, 10%, 15% and 20%) of the MSSA concrete with different curing regime (air and water curing). Furthermore, to analyse its mechanical properties and performance towards aggressive environment. The optimum temperature of burning of MSSA was tested by X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) test. The mechanical properties of MSSA concrete was examined by compressive strength test, flexural Strength and modulus of elasticity after 180 days of curing. While, the performances of the MSSA concrete towards aggressive environment were identified by using Acid Attack test and Sulphate Resistance test. Water absorption test were also conducted to determine the percentage of water absorbed by MSSA concrete. Based on the result, High Temperature Mode was found the best in result compared to Medium and Medium High Temperature Mode. This is due to the high availability of Silicon Dioxide as the important pozzolanic element in the concrete strength development. Water curing with 5% of MSSA (W5) shown the best in results compared to other specimens in term of mechanical properties and its performance towards aggressive environment. The mechanical properties of 5% MSSA content in concrete shows the most optimum samples due to the densification of pozzolanic reaction and filler effect of MSSA. The lowest mechanical performance was sample with 20% content of MSSA for both curing method. The curing effect with better result was water curing, as it shown highest value of strength in all mechanical performance test. Water curing with 5% MSSA (W5) also shows best in durability resistance towards sulphate and acid attack. As conclusion, based on the results, it is shown the positive impact on using the MSSA as additional material to the cement mixture as it improves the quality of the concrete. Thus, this initiative can help in reduce the disposal activity of sewage sludge waste on dumping site and improves the quality performances of the concrete.